RECENSIÓN: Guerra Moreno, Débora (coord.), Constitución y justicia digital, Bogotá, Grupo Editorial Ibáñez, Cúcuta, Universidad Libre, 2021, ISBN: 978-958-791-461-0, 204 pp. - Abal, Lucas O. (Forum, 2022)
...